DETERMINING NOMINAL VALUES OF INPUT PARAMETERS FOR PRODUCTION PROCESS USING DOE - Ignjatovska, Anastasija; Tomov, Mite (Faculty of Technical Sciences, 2021)
Application of statistical methods in quality improvement of molded parts is presented in this paper. Implementation of two stages of DMAIC improvement cycle in a pre-production process is analysed in detail. DOE method is performed to define nominal values of process parameters of injection molding process. A fraction-factorial design with a single central point is used. A linear mathematical model with included elements of second-order interaction is defined. Finally, control stage is performed using prior defined nominal values. Process capability test is conducted in order to determine whether the process is capable of producing parts within specified tolerance field.